2014
DOI: 10.4103/0974-8237.142305
|View full text |Cite
|
Sign up to set email alerts
|

A morphological and morphometric study of jugular foramen in dry skulls with its clinical implications

Abstract: Objective:Jugular foramen of human skull is one of the most interesting foramina. It is a complex bony canal, numerous vital structures, including nerves and vessels are transmitted through it. Most of the intracranial and extra cranial lesions of posterior cranial fossa might affect the structures in jugular foramen in addition to intrinsic abnormalities. As the neurosurgeons have become courageous in approaching this area, so there is a need to become familiar with this area. Hence, the present study was don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 3 publications
7
23
3
3
Order By: Relevance
“…The mean depth of jugular foramen dome is comparable to the results of Singla et al [17] who studied skulls in an Indian population and obtained 11.11 mm and 11.04 mm for the right and left JF respectively. Gupta et al [18] reported a depth of 11.75 mm for the right JF and 11.13 mm for the left JF, these too correspond to the present study. The ranges of the depths do not exhibit such a wide population difference compared to other JF dimensions.…”
Section: Septationsupporting
confidence: 73%
See 1 more Smart Citation
“…The mean depth of jugular foramen dome is comparable to the results of Singla et al [17] who studied skulls in an Indian population and obtained 11.11 mm and 11.04 mm for the right and left JF respectively. Gupta et al [18] reported a depth of 11.75 mm for the right JF and 11.13 mm for the left JF, these too correspond to the present study. The ranges of the depths do not exhibit such a wide population difference compared to other JF dimensions.…”
Section: Septationsupporting
confidence: 73%
“…[20] The population differences are genetic or ethnic based. [10,18,21] Jugular dome suggests a prominent superior jugular bulb which should not be mistaken for a tumor or a mass during radiography. Where the dome is so high that it reaches above the internal acoustic meatus, it is indicative of a high riding jugular bulb.…”
Section: Septationmentioning
confidence: 99%
“…Morphometric studies of skull base foramina are adequate tools for evaluating variability of these anatomic characteristics within groups and comparing said features between populations (Osunwoke et al, 2010;Khan et al;Osunwoke et al, 2012;Gupta et al;Kumar et al;Vidya et al). The importance of characterizing these anatomical features in different populations not only lies within the clinical and pathological realms, as their morphology and morphometry sometimes represent decisive features of the outcome of certain diseases and procedures, but also provides useful information of groups as ethnicities, their genetic profile and the environmental factors they are probably exposed to (Roberts et al;Bhatia et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…From an inferior view, there are ten skull base foramina conventionally described as constant: greater palatine, lesser palatine, lacerum, ovale, spinosum, external opening of the carotid canal, stylomastoid, jugular, mastoid, and external opening of the hypoglossal canal (Drake et al). These structures can be used to establish differences between different populations and ethnic groups, due to the fact that both their morphology and morphometry are particularly variable (Osunwoke et al, 2010;Khan et al, 2012;Osunwoke et al, 2012;Gupta et al, 2014;Kumar et al, 2015;Vidya et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation